Nutrient Contents and Gossypol Levels of Cotton Seed Meal Produced in Hatay Region of Turkey - Kaya, Serafettin; Ustaoglu, Akin (Asian Journal of Chemistry, 2010)
The aim of the study were to determine the nutrient contents and gossypol levels of upland type (Gossypium hirsutum) whole cotton seed and cotton seed meal produced in Hatay region of Turkey as an important potential raw material for animal feeding operations. The whole cotton seed and cotton seed meal materials were seven commercial hybrid seeds, expeller (13 samples) and extraction system (1 sample), respectively. Nutrient analyzes showed that there were significant differences between whole cotton seeds with respect to dry matter (DM), organic matter (OM), ether extract (EE) and ash contents (p < 0.01) while crude protein (CP), nitrogen free extract (NFE) and crude fiber (CF) were not significant between each other (p > 0.05). Free gossypol levels of whole cotton seed were 0.362, 0.440, 0.478, 0.493, 0.510, 0.526 and 0.591 % in GW-Teks, BA-151, BA-320, SG-125, BA-119, Sahin 2000 and BA-308 samples, respectively. The crude protein and ether extract contents of expeller and extraction cotton seed meal were determined 21.50, 40.14 and 9.16, 1.30 %, respectively. Free gossypol level of either extraction or expeller cotton seed meal was 0.06 % in average and no significant difference (p > 0.05). Both nutrient contents and gossypol levels of whole cotton seed and cotton seed meal seemed to be similar with the reported results, except the crude protein content of expeller cotton seed meal.